THE INFLUENCE OF DEMOCRATIC LEADERSHIP, INNOVATIVE BEHAVIOR AND COMMITMENT TO EMPLOYEE PERFORMANCE AT THE TAPIN DISTRICT EDUCATION OFFICE - Naimah, Nadia Jannatun; Hadi, Syamsul; Yulianto, Eko (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
This research aims to understand in depth about the influence between democratic leadership, innovative behavior, and commitment to employee performance. The sample of this study consisted of 51 respondents who worked in the Tapin District Education office. The data collection technique used in this study is a questionnaire which is then processed using a data quality test consisting of validity and reliability tests, classical assumption tests which include normality tests, multicollinearity tests, and heteroscedasticity tests, multiple linear regression tests, and finally hypothesis tests consisting of t tests, F tests, adjusted r square tests. The results concluded that democratic leadership and commitment did not have a significant effect on employee performance. While innovative behavior has a significant effect on employee performance.